Being and appearance : the aporia of Husserlian phenomenology - Lévêque, Gilles (Studies on phenomenological mind, 2025)
Being and Appearance: The Aporia of Husserlian Phenomenology sets out to take phenomenology at its word, with a phenomenological examination of Husserlian phenomenology. More precisely, it's a question of determining what properly shows itself with the transcendent thing, and in what way. This investigation reveals that absence is what properly shows itself with the being of what is given; this is not only with regard to the transcendent thing, but also with regard to consciousness itself as an object for itself. This investigation also reveals that it is illusion that is the specific mode of phenomenality of the transcendent thing, to which being is conferred only because it has the appearance of being real. In the final analysis, it appears that Husserlian phenomenology is torn between two criteria of being: being as pure presence, given as an absolute, and being as the objectivity of the object, i.e. absence. The aporia of Husserlian phenomenology lies in the impossibility of deciding between these two criteria of being.